Optimalisasi Promosi Digital UMKM Raymais Berbasis CapCut dan AISDALSLove - Adinia Novika Ramadhani; Ahmad Fauzi; Dwi Sudjanarti (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
Raymais MSME is a producer of traditional Malang cookies that still faces challenges in utilizing digital media for promotion, causing its product advantages to be communicated suboptimally. This study aims to design, measure the quality of, and evaluate the impact of CapCut-based promotional videos published on TikTok on Raymais MSME's promotional performance. The study employed an action research approach through the stages of planning, action, observation, and reflection. Data were collected through a questionnaire based on the AISDALSLove model and audience interactions on social media. The results showed that optimizing the promotional video improved content quality across all AISDALSLove dimensions. Enhanced storytelling, brand identity, visual quality, and audio attracted audience attention and interest, encouraged information seeking, increased purchase desire and action, and generated positive evaluations, sharing behavior, and emotional attachment to the product. These findings indicate that the CapCut-based promotional video improved the quality of promotional messages, strengthened brand identity, and increased audience engagement, while the AISDALSLove model can serve as a reference for continuous promotional content evaluation.